THE EFFECT OF TWO TRAINING METHODS (PENDULUM AND PLAY) ON DEVELOPING SOME MOTOR ABILITIES FOR ADVANCED TENNIS PLAYERS - Asst. Lect Ahmed Shihab Ahmed; Prof. Dr Haidar Abd AL Razzag; Prof. Dr Makki Jabbar Almajdy (Scholars Digest Publishing, 2024)
The importance of the research is the combination of science and training to find the best training methods in achieving good results for tennis players. With science, it is possible to determine the extent of the player’s ability to perform physically at a constant level and without fatigue during competition and throughout the match period, which sometimes exceeds more than (6) hours. After knowledge, it is possible to develop the appropriate training method to adapt to that environment, as in the pendulum training and playing methods, and continue training in it for the purpose of entering the competition and completing the match without falling in level. The research community was limited to the advanced players of Basra Governorate tennis clubs, which numbered (3) clubs. The most important objectives of the research were: Identifying the effect of the two training methods (pendulum and play) on developing some motor abilities of advanced tennis players. It was concluded: The two training methods (pendulum and play) achieved the goals of sports training in developing some of the motor abilities of advanced tennis players.
Keywords: pendulum training, playing training, motor abilities, tennis